ANALISIS PENGARUH KOMPENSASI, KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN (Studi pada Karyawan PT Barata Indonesia (Persero) Gresik – Jawa Timur) - Ramadhani, Dwiki Satria; Rahardjo, Mudji (Diponegoro Journal of Management, 2016)
Global competition force big companies or small to more aware of employee performance.Performance derived from a job performance having meaning work performance or work performance indeed reached someone.Companies are required to more attention to the quality of human resources owned by giving the things needed to optimize performance employees.A good performance is a conducted in optimal with conformity upon default organizations and support the purpose company.The success of an organization influenced by the performance of ( job performance ) human resources, for that each company will try to improve the performance employees in achieving its objectives organization on whom it is setThis research aims to analyze the effect of variables of compensation,organizational commitment and transformational leadership style on employee performance. This research was conducted at PT Barata Indonesia (Persero) Gresik – East Java. The sample used in this research were employees of PT Barata Indonesia (Persero) Gresik – East Java 78 people in total. The sampling technique was conducted using Purposive Sampling.This research shows that compensation,organizational commitment and transformational leadership style on employee performance influence positively and significantly to the employee performance.Value of determination coefficient (R2) is 0,760 or 76%. This means variable compensation , the organization and style transformational leadership explain the employee performance amounted to 76 %.